2005
DOI: 10.1016/j.jhazmat.2005.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of organic matter and trihalomethane formation potential in reclaimed water from treated industrial estate wastewater by coagulation

Abstract: Raw water from treated industrial estate wastewater in northern Thailand was used in jar-test coagulation experiments with variations of separate alum and ferric chloride dosages from 10 to 80 mg/L at pH conditions ranging from 5 to 6.5. Natural organic matter (NOM) surrogates and trihalomethane formation potential (THMFP) were determined to study their reduction. The obtained results showed that total organic carbon (TOC) were gradually reduced from the average value of about 6.1 mg/L to a level of about 4.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…The removal trends are consistent with those seen in drinking water treatment [25]. In addition, the optimum pH for DOC removal in ferric chloride coagulation has also been observed to be 5 for wastewater [19]. As mentioned in literature [25], iron hydroxide flocs are more positively charged at acidic pH values.…”
Section: Doc Removalsupporting
confidence: 87%
See 1 more Smart Citation
“…The removal trends are consistent with those seen in drinking water treatment [25]. In addition, the optimum pH for DOC removal in ferric chloride coagulation has also been observed to be 5 for wastewater [19]. As mentioned in literature [25], iron hydroxide flocs are more positively charged at acidic pH values.…”
Section: Doc Removalsupporting
confidence: 87%
“…El Samrani et al [18] investigated the nature of coagulant species formed during the clarification of municipal sewage with a commercial ferric chloride. Musikavong et al [19] studied the reduction of organic matter and trihalomethane formation potential in reclaimed water from treated industrial estate wastewater by coagulation. Amuda and Alade [20] examined the removal of chemical oxygen demand (COD), total suspended solids (TSS), and total phosphorus (TP) in abattoir wastewater by coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…The UV 254 generally decreases with increasing ferric dose, indicating preferential removal of the humic fraction. As a comparison with Musikavong et al, study, they found that the removal of aromatic substances by alum and ferric chloride coagulation is more effective than the removal of DOC, and it can be concluded from these results that bigger aromatic molecules are removed more effectively than both smaller aromatic molecules (Musikavong et al, 2005). This result supports the conclusion that TLW's NOM was as amenable to chemical coagulation because of its moderate humic fraction.…”
Section: Resultssupporting
confidence: 66%
“…Iron salts achieving better organic removal than alum salts have been reported in a number of literatures [20][21][22]. In addition, chloride-based metal salts removed more COD by almost 10% than sulfate-based ones, which implies that counter-ions introduced as anions can have a significant effect on the coagulation process.…”
Section: Hpsec Chromatogramsmentioning
confidence: 96%